Who benefits from farmer-led irrigation expansion in Ethiopia? - Kafle, Kashi; Omotilewa, Oluwatoba; Leh, Mansoor (African Development Bank, 2020)
Despite increasing popularity of farmer-led irrigation in Ethiopia, little is known about socio-economics of farmers who receive public support in accelerating its expansion. We investigate this question by combining spatial land suitability for groundwater- and solar irrigation with pre-existing socioeconomic data. We find that if public support in farmer-led irrigation expansion were to be provided to farmers who own land areas that are also spatially highly suitable for irrigation, high-value crop cultivators and wealthier farmers would most likely benefit from such investments. Specifically, we find evidence that farmers in land areas more suitable for groundwater irrigation cultivated more high value crops such as vegetables, fruits, and cash crops. Cultivation of staple crops such as cereals, oilseeds, legumes and root crops were negatively associated with groundwater irrigation suitability. In addition, we find a positive correlation between farmers’ wealth status (measured by consumption expenditure, asset index, and land size) and groundwater irrigation suitability. Controlling for regional differences and current irrigation coverage, one percent increase in irrigation suitability score was associated with 0.2% increase in per-capita consumption expenditure. Land areas that were suitable for irrigation were more likely to belong to large-holders than smallholders. Results imply that policies which aim to facilitate farmer-led irrigation development in Ethiopia should not rely only on spatial suitability for irrigation. Household socio-economics and existing agricultural practices are equally important.